2011
DOI: 10.4103/2230-8229.83375
|View full text |Cite
|
Sign up to set email alerts
|

Breast abscess caused by penicillin resistant Pneumococci

Abstract: Breast abscess is mostly caused by Staphylococcus aureus. A 26-year-old immunocompetent lady was admitted with breast abscess. Incision and drainage (I/D) was done and Pneumococci were isolated from the drained pus. The patient was earlier treated with Augmentin which was later changed to linezolid after testing for antibiotic susceptibility. This strain showed a high level of resistance to penicillin. It had been noticed that there was a slow increase in the number of penicillin resistant Pneumococci isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…To date, 6 cases of pneumococcal mastitis have been reported, only 1 of which was nonpuerperal (Table 1). 3–8 The present case, the second instance of pneumococcal mastitis in a nonlactating, pregnant patient, demonstrated that pneumococcal mastitis has the potential to develop into a severe systemic condition, such as IPD, which can lead to serious fetal status.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…To date, 6 cases of pneumococcal mastitis have been reported, only 1 of which was nonpuerperal (Table 1). 3–8 The present case, the second instance of pneumococcal mastitis in a nonlactating, pregnant patient, demonstrated that pneumococcal mastitis has the potential to develop into a severe systemic condition, such as IPD, which can lead to serious fetal status.…”
Section: Discussionmentioning
confidence: 62%
“…Streptococcus pneumoniae rarely causes mastitis, and only a few cases have thus far been reported. [3][4][5][6][7][8] Although pneumococcal mastitis in puerperal women may be due to pneumococcal transmission from their child during breastfeeding, 4,5 a case of nonlactational pneumococcal mastitis in a patient with systemic lupus erythematosus (SLE) has been reported. 3 Although the risk factors of pneumococcal mastitis are not well known, previous studies reported an association between SLE and an increased susceptibility to invasive pneumococcal diseases (IPDs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient was an immunocompetent 37-year-old woman with no signs of any underlying disease. Although it has been stated that healthy breast-feeding women may harbour potentially pathogenic bacteria in their breast milk [ 2 ], the purulent material expelled from the nipple and the fact that pneumococci may cause breast abscess [ 8 ] prompted initiation of empiric antibiotic therapy, which was continued for a short while as it was relevant to the results of the antibiotic susceptibility testing.…”
Section: Discussionmentioning
confidence: 99%